2021
DOI: 10.1177/1834490920974761
|View full text |Cite
|
Sign up to set email alerts
|

Self-Worth and Self-Knowledge in Iranian Patients Seeking Cosmetic Surgery: A Comparative Study

Abstract: Prior research has reported a psychological impairment in patients seeking cosmetic surgery. However, the role of other variables such as contingencies of self-worth and self-knowledge has been ignored. Hence, the aim of this study was to examine new psychological structures, contingencies of self-worth, and self-knowledge among patients seeking cosmetic surgery. Eighty patients (47 female and 33 male; mean age = 28.98, SD = 8.32; 40 seeking cosmetic surgery and 40 seeking surgical treatment) were randomly rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…46 However, in the study of Valikhani et al in Iran, there was no significant difference between the two groups seeking cosmetic surgery and the control group in terms of depression, anxiety, stress, and vitality. 47 According to the regression model in this study, the history of having cosmetic surgery had a significant relationship with female gender and having symptoms of mental disorder, while it had no relationship with education, income, marital status, employment status, and spiritual health. In the study of Bidkhori et al in Tehran, the prevalence of cosmetic surgery was significantly related to gender and was 2.3 times higher among women than men.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…46 However, in the study of Valikhani et al in Iran, there was no significant difference between the two groups seeking cosmetic surgery and the control group in terms of depression, anxiety, stress, and vitality. 47 According to the regression model in this study, the history of having cosmetic surgery had a significant relationship with female gender and having symptoms of mental disorder, while it had no relationship with education, income, marital status, employment status, and spiritual health. In the study of Bidkhori et al in Tehran, the prevalence of cosmetic surgery was significantly related to gender and was 2.3 times higher among women than men.…”
Section: Discussionmentioning
confidence: 76%
“…In another study in Iran, mental disorders (depression, anxiety, aggression, morbidity, obsessive‐compulsive disorder, and sensitivity in relationships) were significantly higher in cosmetic surgery applicants than non‐applicants 46 . However, in the study of Valikhani et al in Iran, there was no significant difference between the two groups seeking cosmetic surgery and the control group in terms of depression, anxiety, stress, and vitality 47 …”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Valikhani et al and Ghorbani et al showed that individuals with limited self-knowledge are less flexible in controlling their thoughts and emotions, ignore their psychological and physical reactions to stressful events, and, as a result, cannot make the necessary modifications. In addition, individuals with high self-awareness tend to be self-integrative and combine negative and positive beliefs that automatically reduce cognitive distortions of the environment and create an accurate and factbased imagination of self (17,32). The study by Shariat et al showed that individuals with integrative selfknowledge are optimistic and resilient in communication and interaction with others and have no depression and unreasonable self-criticism (18) In addition, previous studies showed a positive relationship between self-knowledge and psychological protective factors, such as self-compassion, mindfulness, psychological well-being, self-esteem, constructive thinking, more consistent assessment of emotions (12), and a negative relationship between selfknowledge with anxiety and perceived stress (17), rumination, and suppression of emotions (13,14,19).…”
Section: Mentalmentioning
confidence: 99%
“…In addition, individuals with high self-awareness tend to be self-integrative and combine negative and positive beliefs that automatically reduce cognitive distortions of the environment and create an accurate and factbased imagination of self (17,32). The study by Shariat et al showed that individuals with integrative selfknowledge are optimistic and resilient in communication and interaction with others and have no depression and unreasonable self-criticism (18) In addition, previous studies showed a positive relationship between self-knowledge and psychological protective factors, such as self-compassion, mindfulness, psychological well-being, self-esteem, constructive thinking, more consistent assessment of emotions (12), and a negative relationship between selfknowledge with anxiety and perceived stress (17), rumination, and suppression of emotions (13,14,19). Therefore, it is expected that the rate of self-criticism and other psychological damage associated with it, including suicide, decreases with the increase of integrative self-knowledge (19).…”
Section: Mentalmentioning
confidence: 99%